Development and analytical performance testing of a novel sTREM2 ELISA method to support drug development. (31st December 2021) - Stoops, Erik; Demeyer, Leentje; Francois, Cindy; Engelborghs, Sebastiaan; Bjerke, Maria; Dage, Jeffrey L.; Wang, Hong
Abstract: Background: The triggering receptor expressed on myeloid cells 2 (TREM2) is a cell surface receptor of microglia cells in the central nerve system and is associated with neuroinflammation. sTREM2 can be used as pharmacodynamic biomarker for inflammation or microglial activation in therapeutic development programs. There is a need for well characterized assays that are suitable for measurement of neuroinflammatory biomarkers in pre‐clinical and clinical drug development. This abstract describes the characterization of a new robust sTREM2 prototype immunoassay based on monoclonal recombinant rabbit antibodies(mAbs). Method: A colorimetric sandwich ELISA was developed using capture mAb B02 (code ADx601) and detector mAb C10 (code ADx602) reactive towards the sTREM2 extracellular ectodomain (aa 19‐172). The analytical assay performance will be reported: the repeatability and reproducibility was determined using a neat CSF based QC panel (n=3; 6 test runs; duplicate testing). Accuracy was assessed by testing parallelism and calibrator point back calculated concentrations. Passing Bablok regression analysis was used to demonstrate consistency of sample testing results (43 samples; duplicate testing; 3 test runs). Finally clinical routine CSF samples were analysed (19 patients diagnosed with AD and 20 controls based upon biomarker profile). Result: A prototype sTREM2 ELISA assay was used to generate the assay characterization data: The %CV for repeatability respectively reproducibility were <12.2% and 15.4%. Accuracy: a slope value of 0.992 was obtained after Deming regression between the theoretical and experimentally obtained levels of 8 samples diluted over the measuring range (25‐3500 pg/mL) while the accuracy of the calibrator points was between 0 and 12.6% difference in back calculated concentration over 6 runs. Testing of the lot consistency (Figure 1) resulted in a slope and intercept value of respectively 1.07 (95%CI: 0.90‐1.17) and ‐80.9 (95%CI: ‐294.70‐154.30).Testing of clinical samples showed an increased sTREM2 concentration in AD versus controls (p<0.01). Conclusion: A novel CSF prototype ELISA for sTREM2 was developed and characterized including lot consistency, precision, accuracy and others. The generated data indicate a robust sTREM2 immunoassay for use in drug development programs. The next step is the transfer to a manufacturing environment to make the assay available as a commercial test kit (RUO).